Importance of fish for food and nutrition security among First Nations in Canada - Marushka, Lesya (Can J Public Health, 2021)
OBJECTIVE: To investigate the relationships between fish/seafood consumption patterns and food security status among First Nations (FN) communities in Canada. We estimated the contribution of fish/seafood to daily nutrient requirements. Barriers to traditional food (TF) access including fish were summarized. METHODS: Data were collected by the First Nations Food, Nutrition and Environment Study (2008–2018). The sample of this participatory study comprised 6258 randomly selected FN adults. Fish/seafood consumption was estimated with a food frequency questionnaire. Food security status was assessed with the Household Food Security Survey Module. The contribution of fish/seafood to protein, n-3 fatty acid, vitamin (A, B12, D, niacin) and mineral (selenium, zinc) requirements was assessed by comparison to Dietary Reference Intakes. RESULTS: Regional differences were observed in fish/seafood consumption patterns and their relationship with food security status. In the eastern regions (Ontario, Quebec/Labrador and the Atlantic region), consumption of fish/seafood and other TF was significantly higher among food insecure compared with food secure FN participants. Severely food insecure men (particularly in British Columbia, Alberta, Quebec/Labrador and the Atlantic region) tended to eat a higher amount of TF, including fish/seafood, compared with food secure and moderately food insecure men, while no difference was observed in women. Fish/seafood provided good sources of selected nutrients. However, the high cost of harvesting equipment, industry-related activities and climate change reduce access to fish/seafood and other wildlife. CONCLUSION: Fish/seafood continues to be vital to the diet of FN communities. Focusing on policies that support FN increased access to fish/seafood has the potential to decrease food insecurity and support sustainable livelihoods. Future policies should focus on socio-economic determinants of food insecurity and support traditional harvesting and sustainable fisheries among FN communities. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.17269/s41997-021-00481-z.